Actividades dramáticas y habilidades sociales en niños de la institución educativa inicial N°386 Bellavista Callarú, Ramón Castilla 2024 - Bento Alexandrez, Ana Rita (2025)
The focus of this study was to identify the relationship between dramatic activities and the development of social skills in the children of the Institución Educativa Inicial N°386 Bellavista Callaru, Ramón Castilla 2024. This study is distinguished by its quantitative approach, using a non-specific design. experimental, correlational and transectional. The sample was made up of 139 children from the aforementioned institutions. For data collection, the observation technique is used, supported by a structured guide as an instrument. The validity of said instrument was guaranteed through an exhaustive review carried out by a panel of experts with extensive experience in the area. The results obtained, which reflect a significant evaluation between dramatic activities and social skills (coefficient of 0.741 and p<0.01), allow us to reject the null hypothesis, which postulated the absence of a relationship between both variables. Consequently, the findings support the main hypothesis that the implementation of dramatic activities positively affects the development of children's social skills.